Responses of four varieties of carrot plant (Daucus carota L.) grown in medium latitude to different dosages of fertilization. Issue 1 (January 2021) - Nikmatullah, A; Zawani, K; Muslim, K; Sarjan, M
Abstract: A study was conducted to investigate the effect of different rates of NPK fertilization on growth and yield of carrot plants in medium latitude. The experiment was undertaken in Setiling Village, Central Lombok (at ca . 650 m amsl) and arranged according to a RCBD two factors: variety (v) and dosages of NPK fertilization (n). The first factor were four carrot varieties: Gundaling (v1), Kirana (v2), New Nantes (v3) and New Kuroda (v4), while the second factor were four dosages of NPK fertilization: 50 kg/ha (r1), 100 kg/ha (r2), 200 kg/ha (r3) and 400 kg/ha (r4). The results showed that there was no interaction between carrot varieties and rate of NPK fertilization on influencing growth and yield of carrot in medium latitude. However, growth and yield of carrot in medium latitude were significantly influenced by variety and rate of NPK fertilization, as shown by differences in the ratio of above and below ground biomass, tap-root weight, tap-root diameter and the ratio between cortex and stele. Accordingly the suitable variety for cultivation in the medium latitude was Gundaling variety (v1), with a higher growth and yield were obtained by NPK fertilization at rate of 200 kg/ha (n3).